Analyzing the Security and Safety Issues of Bluetooth Technology (International Journal of Food and Nutritional Sciences, 2022)
With its ability to transmit wirelessly across short distances at a cheap cost and with little power consumption, Bluetooth technology has become an indispensable component of the modern world. The 2.4GHz frequency band is what Bluetooth uses. The security risks in the Bluetooth network include unauthorized access by hostile parties, the possibility of internal assaults via ad hoc transmissions, the extraction of data undetected, the possibility of data corruption on wireless devices from viruses or other susceptible attacks, etc. The security sectors are becoming more vulnerable, which might be risky for the privacy of personal data of the user. Network security for Bluetooth is proposed to address these problems. Therefore, the aim of this paper is to review the security and safety issues of the Bluetooth technology and the discussion on the basic of security methods of Bluetooth.